2017
DOI: 10.1038/s41535-017-0035-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantum ferromagnet in the proximity of the tricritical point

Abstract: Echoes of quantum phase transitions at finite temperatures are theoretically and experimentally challenging and unexplored topics. Particularly in metallic quantum ferromagnets the experimental investigations are hampered by an intricate preparation of sufficiently pure samples and the access to the proper coordinates in parameter space. The present study shows that it is possible to tune a specific system at easily accessible conditions to the vicinity of its quantum phase transition. The physics is demonstra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…This is also seen in change of critical exponent β, which differs from other crystals. If we compare the residual resistivity of the SC2A900 sample with those available in literature of other members of the UTX family with the ZrNiAl crystal structure, we see that the best values are of the order of 10 μΩ.cm (URhAl [15], UCoAl [3,16], UNiGa [17]). These values are fully comparable to the best values obtained in this study.…”
Section: Discussionmentioning
confidence: 97%
“…This is also seen in change of critical exponent β, which differs from other crystals. If we compare the residual resistivity of the SC2A900 sample with those available in literature of other members of the UTX family with the ZrNiAl crystal structure, we see that the best values are of the order of 10 μΩ.cm (URhAl [15], UCoAl [3,16], UNiGa [17]). These values are fully comparable to the best values obtained in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Similar experimental studies have revealed other wing-structure phase diagrams in UGe 2 [8,30,31] (also shown in Fig. 6 for comparison), Sr 3 Ru 2 O 7 [37], ZrZn 2 [9], UCoAl [35,36,40]. The behavior near the tricritical point could not be studied in Sr 3 Ru 2 O 7 and UCoAl because those compounds are already in the paramagnetic regime at ambient pressure.…”
Section: Quantum Wingmentioning
confidence: 92%
“…The behavior near the tricritical point could not be studied in Sr 3 Ru 2 O 7 and UCoAl because those compounds are already in the paramagnetic regime at ambient pressure. Substitutions studies revealed the existence of a nearby tricritical point in UCoAl [40]. In ZrZn 2 , the tricritical point is near 3 K, making the experimental investigations difficult.…”
Section: Quantum Wingmentioning
confidence: 99%
“…The very strong uniaxial magnetic anisotropy locks the U magnetic moments aligned along the c-axis of the hexagonal structure whereas only Pauli paramagnetism is observed in the perpendicular directions. Several these compounds order ferromagnetically providing a playground for investigation of the critical behavior of itinerant ferromagnets [2][3][4][5]. Contrary to the case of antiferromagnetism where novel states are result of the presence of quantum critical point (QCP; see e.g.…”
Section: Introductionmentioning
confidence: 99%